Comparison of manual and automatic approaches for characterisation of morphology and nanostructure of soot particles. (October 2019) - Verma, Puneet; Pickering, Edmund; Savic, Natascha; Zare, Ali; Brown, Richard; Ristovski, Zoran
Abstract: This study is an attempt to compare the manual and automatic approaches for analysis of the morphology and nanostructure of soot particles. The automated methodology is composed of two parts: soot particle analysis (morphology characterisation) and soot fringe analysis (nanostructure characterisation) such as fringe length, fringe tortuosity and fringe separation distance. In this study the application of Fast Fourier Transform (FFT) is introduced, which omits the manual selection of fringe pairs for measurement of fringe separation distance and aids fast computation. The parameters which effect the performance of automated approach were identified and optimised. The automated approach was applied to analyse images from different fuels. Using the optimised parameters, the performance of the automatic approach was tested against results obtained by the manual approach. The statistical comparison between two approaches showed similar results but with better accuracy for automated approach (lower standard error) and thus validates the functionality of the proposed methodology. The application of FFT in computation of fringe separation distance reduces the computation time and avoids biases of operator in selecting fringe pairs. Graphical abstract: Image 1 Highlights: The manual and automatic approaches for analysis of the morphology and nanostructure of soot particles are compared. Fast Fourier transform (FFT) is applied for calculation of fringe separation distance. The comparison between manual and automated approaches showed similar results with better accuracy.